ANALYSIS AGAINST ARREST SUSPECT IN POLICE REGULATION NO. 14 YEAR 2012 ON THE CRIME INVESTIGATION MANAGEMENT (CASE STUDY IN NORTH BOGOR POLICE) - Dadang Suprijatna; Indralis Wardana; Fahrul Siregar (JURNAL HUKUM DE'RECHTSSTAAT, 2015)
ABSTRACTThe method used in this thesis is a normative juridical research that is the approach that uses the concept of positive legality which states that the law is identical with the norms made written and enacted by institutions or authorities. In addition this concept also saw law as a normative system that is autonomous, closed and detached from public life. For the purposes of the investigation, investigators at the behest of investigators authorized to make arrests also for the sake of the investigation, the investigator and the investigator maid authorities make arrests. Arrest order made against a person who alleged a criminal offense based on sufficient preliminary evidence. Execution of tasks arrests were made by police officers of the Republic of Indonesia by taking into account the Letter of Assignment and gives an arrest warrant that lists the suspect's identity and mentions the reason for arrest and brief descriptions of crimes that presupposed and place in check, in which case caught arrests made without warrants, provided that the catcher should be immediately handed caught and existing evidence to the investigator or the investigator's closest aides, ransom arrest warrant should be given to the family immediately after the arrest is done, can be done for a maximum of one day. The conclusion of this study are 1) The arrest of the perpetrators of the process by members of the police force North Bogor Police first is the start of the search for information, arrest / raids, searches of perpetrators, confiscation of evidence to facilitate the examination of the offender. 2) Barriers experienced by members of the North Bogor Police in the execution of the arrest of a criminal offense (a) Lack of cooperation between the police (investigators) to the public; (b) Perpetrators of the crime of removing traces of the crime; (c) Limited facilities and prasarana.yang owned by North Bogor Police; (d) .Terbatasnya human resources (police) to uncover a crime. 3) Efforts by the North Bogor Police to overcome the obstacles in the process of the arrest of perpetrators of criminal acts as follows: (a) Fix yourself to socialize paradigm shift to community policing. (b) Provide an opportunity for the whole society to provide input to the North Bogor Police. (c) Guidance personnel are able to provide persuasive measures. (d) Propose to the City Police Bogor on procurement operational support facilities.